Podemos ayudar? : ninos que ayudan a sus comunidades - Ancona, George; Mlawer, Teresa (Somerville, Massascusetts : Candlewick Press, 2019)
Children train dogs to help those with disabilities; kids tutor younger kids in a special after-school program. Readers meet the child volunteers dedicated to helping out as their inspirational tales show young readers how to lend a helping hand, themselves.
5-8.
In Spanish.
Keywords: Voluntarism -- Juvenile literature; Volunteers -- Juvenile literature; Humanitarianism -- Juvenile literature; Voluntarios -- Literatura juvenil